Equanimity of Risk and Return Relationship between Shariah Index and General Index in India - Dharani, M. (Journal of Economics and Behavioral Studies, 2011)
The present study empirically examines the risk and return of the Nifty Shariah index and Nifty index during the period 2nd January 2007 to 31st December 2010. The sample period is further divided into bull market period and bear market period based on the movement of the both indices during the study period. The objective of the study is to analyse the performance of the Islamic index and common index and to test whether any significant difference between both indices in India. Based on the previous studies, the present paper employs Risk adjusted measurement such as Sharpe index, Treynor Index and Jensen alpha. The t- test is used to test the mean returns difference between both indices. The study found that Nifty Shariah has been underperformed during the sample and sub sample period. According to ttest, the mean difference between both indices has not been significant which reveals both are consistent. The risk adjusted returns for the both indices reveals that both were underperforming with respect to risk free rate of return. The study has also disclosed the low volatile nature of Nifty Shariah than Nifty index. Finally, the study concludes that Nifty Shariah and Nifty indices in India are performing in a similar manner.